2017
DOI: 10.1002/rmb2.12025
|View full text |Cite
|
Sign up to set email alerts
|

Possible ability of bovine follicular fluid to attract migrating bull spermatozoa

Abstract: AimTo examine the potential of bovine follicular fluid (BFF) to attract bull spermatozoa.MethodsThe ability of the BFF to attract bull sperm was evaluated by observing changes in sperm migration after being placed in a cross‐column chamber. The movement parameters of the heads and flagella of the sperm that were attracted to the BFF were analyzed by using the Computer Assisted Sperm Analysis system.ResultsIt was observed that 61.6% of the bull sperm migrated toward the BFF when the BFF was used at a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…It was also found that SDF1 is not a regulatory factor of sperm protein tyrosine phosphorylation, which is a major indicator of sperm capacitation, or the acrosome reaction (S5 Fig). According to our results, <5% of total sperm were attracted by SDF1, which was in agreement with previous studies suggesting that only a small fraction of the sperm population is chemotactically responsive in mammals [6,18,33]. In fact, the percentage of chemotactic sperm in the total sperm population is 2%-12% in humans [34].…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…It was also found that SDF1 is not a regulatory factor of sperm protein tyrosine phosphorylation, which is a major indicator of sperm capacitation, or the acrosome reaction (S5 Fig). According to our results, <5% of total sperm were attracted by SDF1, which was in agreement with previous studies suggesting that only a small fraction of the sperm population is chemotactically responsive in mammals [6,18,33]. In fact, the percentage of chemotactic sperm in the total sperm population is 2%-12% in humans [34].…”
Section: Plos Onesupporting
confidence: 93%
“…Several studies have demonstrated that only capacitated sperm, which possess the potential to undergo the acrosome reaction and hyperactivation, are chemotactic in humans and mice [32,33,35]. However, in cattle, the capacitated state is unlikely to be relevant to sperm chemotaxis because this study and a previous study showed that sperm capacitation treatment is unnecessary to induce sperm chemotaxis in cattle [18]. It should be noted that in this study, the sperm medium contained caffeine that induces hyperactivation immediately regardless of the sperm capacitated state (S6 Fig) [36].…”
Section: Plos Onementioning
confidence: 54%
See 1 more Smart Citation
“…This synchronicity allowed for the identification of extracellular Ca 2+ entry via CatSper channels of the flagellar principal piece, and Ca 2+ release from internal storage within the connecting piece as important initiators of hyperactivation as well as sperm fertility (Carlson et al, 2003(Carlson et al, , 2005Marquez, Ignotz, & Suarez, 2007). Conversely, achieving high rates of synchronous hyperactivation in ejaculated spermatozoa of livestock is not easily done by incubation in capacitation medium containing bicarbonate (Marquez & Suarez, 2004;McPartlin, Suarez, Czaya, Hinrichs, & Bedford-Guaus, 2009;Mondal, Takagi, Baba, & Hamano, 2017;Umezu et al, 2016), so regulatory mechanisms for their hyperactivation are instead investigated in samples pharmacologically treated with possible elevators of intracellular Ca 2+ (e.g., the Ca 2+ ionophore A23187; procaine; 4-aminopyridine (4-AP); caffeine; thapsigargin; or thimerosal) (Ho & Suarez, 2001;Marquez & Suarez, 2004;McPartlin et al, 2009;Tateno & Mikamo, 1987;Schmidt & Kamp, 2004;Suarez, Dai, DeMott, Redfern, & Mirando, 1992). This extra step limits out understanding how sperm alterations lead to their hyperactivation in livestock.…”
mentioning
confidence: 99%
“…Estes resultados são sugestivos de cinética de hiperativação, pois não há consenso sobre os valores destes parâmetros que caracterizam este tipo de cinética espermática na espécie bovina, sendo encontrados valores divergentes na literatura (SHOJAEI et al, 2012;VAN DER HORST, 2014;KANNO et al, 2017;MONDAL et al, 2017). A dificuldade no estabelecimento destes valores de referência e ainda, a comparação de resultados em diferentes estudos, é de grande complexidade devido a diversos fatores que influenciam na acurácia e precisão desta avaliação, como: metodologia, uso de diferentes tipos de aparelhos e configurações do software, manipulação de amostras como meio diluir e seleção espermática (SHOJAEI et al, 2012;WABERSKI, 2014;ISHIJIMA, 2015;DEL GALLEGO et al, 2017;KANNO et al, 2017).…”
Section: Cinética Espermáticaunclassified